Southeast Asia and the Civil Society Gaze : Scoping a Contested Concept in Cambodia and Vietnam - Waibel, Gabi; Ehlert, Judith; Feuer, Hart N.; Waibel, Gabi; Ehlert, Judith; Feuer, Hart N. (Taylor & Francis, 2014)
As developing countries with recent histories of isolation and extreme poverty, followed by restoration and reform, both Cambodia and Vietnam have seen new opportunities and demands for non-state actors to engage in and manage the effects of rapid socio-economic transformation. This book examines how in both countries, civil society actors and the state manage their relationship to one another in an environment that is continuously shaped and (re)constructed by changing legislation, collaboration and negotiation, advocacy and protest, and social control. Further, it explores the countries$1 (Bdivergent experiences whilst also uncovering the underlying basis and drivers of civil society activity that are shared by Cambodia and Vietnam. Crucially, this book engages with the contested nature of civil society and how it is socially constructed through research and development activities, by looking at contemporary discourses and manifestations of civil society in the two countries, including national and community-level organisations, associations, and networks that operate in a variety of sectors, such as gender, the environment and health. Drawing on extensive fieldwork conducted in Cambodia and Vietnam, this book will be of huge interest to students and scholars of Southeast Asian studies, Southeast Asian politics, development studies and civil society.s
English
Keywords: Ethnic studies; Development studies; Regional studies; bach; cambodian; community-based; mass; organizations; quy; sinh; tan; thi; vietnamese